2020
DOI: 10.1097/rmr.0000000000000248
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Reality to Relieve Pain in Burn Patients Undergoing Imaging and Treatment

Abstract: Pain from burn injuries is among the most excruciating encountered in clinical practice. Pharmacological methods often fail to achieve acceptable level of analgesia in these patients, especially during burn wound dressing and debridement. Virtual reality (VR) distraction is a promising analgesic technique that progressed significantly in the last decade with development of commercially available, low-cost, high-resolution, wide field-of-view, standalone VR devices that can be used in many clinical scenarios. V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 52 publications
0
13
0
Order By: Relevance
“…The potential psychological mechanism is shown in gate control theory (Melzack and Wall 1965) such that VR induces attentional shifting with less cognitive focus on the noxious stimuli, resulting in a decrease in the experience of pain and anxiety (Gold et al 2007;Triberti et al 2014). VR has been demonstrated to modulate pain-related brain activity at the cortical and subcortical levels, which correlated with subjective improvement in pain perceptions (Hoffman et al 2006;Hoffman et al 2007;Bermo et al 2020). We hypothesized that VR distraction would attenuate patients' anxiety and pain and consequently maintain the BP and HR.…”
Section: Introductionmentioning
confidence: 99%
“…The potential psychological mechanism is shown in gate control theory (Melzack and Wall 1965) such that VR induces attentional shifting with less cognitive focus on the noxious stimuli, resulting in a decrease in the experience of pain and anxiety (Gold et al 2007;Triberti et al 2014). VR has been demonstrated to modulate pain-related brain activity at the cortical and subcortical levels, which correlated with subjective improvement in pain perceptions (Hoffman et al 2006;Hoffman et al 2007;Bermo et al 2020). We hypothesized that VR distraction would attenuate patients' anxiety and pain and consequently maintain the BP and HR.…”
Section: Introductionmentioning
confidence: 99%
“…In other words, the brain can send signals down to the spinal cord, which reduce (or in some cases increase) the amount of nociceptive signals allowed to travel from the spinal cord to the brain. This control system has a cortical component at the anterior cingulate and prefrontal cortex and subcortical components at certain brainstem nuclei ( 3 , 25 , 34 39 ). A small but important study in two subjects who are “pain-free” due to SCN9A mutation, showed activation of the pain matrix during laboratory mechanical pain applied to the dorsum of their hand, similar to response in 4 normal control subjects ( 40 ).…”
Section: Imaging Of Painmentioning
confidence: 99%
“…A pain processing network model by Garcia et al ( 29 ) suggested that pain is processed at three levels, at an unconscious level processed in peri-Rolandic cortex and limbic system receiving afferent spinothalamic pain signals, at an intermediate awareness level processed at fronto-cingulate-parietal networks in addition to the sensorimotor cortices, and at a higher conscious extended level which includes adding input from memories and self-awareness. The comprehensive pain experience processing network appears to include more regions with contribution from other cortical and subcortical cerebral regions such as the brain stem and the cerebellum ( 3 , 29 ).…”
Section: Imaging Of Painmentioning
confidence: 99%
See 1 more Smart Citation
“…The patterns of pain-related brain activity during wound care were temporarily "frozen in time". In the study by Bermo et al (2020), the patient received their usual painful burn wound care/scrubbing in the wound care room, with their usual wound care nurse. Patients received an injection of the tracer, but no scan during wound care.…”
Section: Mechanism Of Actionmentioning
confidence: 99%